Interpreting the Spectrotemporal Properties of the Black Hole Candidate Swift J151857.0-572147 during Its First Outburst in 2024 - Kaushik Chatterjee; S. Pujitha Suribhatla; Santanu Mondal; Chandra B. Singh (The Astrophysical Journal)
The transient Galactic black hole candidate Swift J151857.0-572147 went through an outburst in 2024 March for the first time. Using publicly archived Insight-HXMT data, we have analyzed the timing and spectral properties of the source. We have extracted the properties of the quasiperiodic oscillations (QPOs) by fitting the power density spectrum, which inferred that the QPOs are of type C. We have detected QPOs up to ∼48 keV using an energy dependence study of the QPOs. A high-frequency QPO was not observed during this period. We also conclude that the oscillations of the shock in transonic advective accretion flows may be the possible reason for the origin of the QPOs. In the broad energy band of 2–100 keV, simultaneous data from the three onboard instruments of Insight-HXMT were used to perform spectral analysis. Different combinations of models, including a broken power law, a multicolor disk blackbody, interstellar absorption, nonrelativistic reflection in both neutral and ionized medium, and relativistic reflection, were used to understand the spectral properties during the outburst. We discovered that at the beginning of the analysis period, the source was in an intermediate state and later transitioning toward the soft state based on the spectral parameters. It has a high hydrogen column density, which could be due to some local absorption by the source.